PENGARUH SUASANA TOKO, KUALITAS PELAYANAN, KEPERCAYAAN, DAN PERSEPSI HARGA TERHADAP MINAT BELI ULANG - Monita Nugrahaeni; Ahmad Guspul; Hermawan Hermawan (Jurnal Fokus Manajemen Bisnis, 2021)
This study aims to investigate the effect of store atmosphere, service quality, price perception, and trust on the repurchase intention of Ayam Susan Wadaslintang. The sampling method of this study was the non-probability sampling by using the accidental sampling technique to 100 consumers. The data then being analyzed statistically by using multiple linear regression analysis, validity test, reliability test, and t-test. The result of the study shows that store atmosphere, service quality, price perception, and trust have a positive effect on consumer repurchase intention.